Mixtures of methanol and 2-propanol as a potential fuel for direct alcohol fuel cells - Gojković S.Lj.; Tripković A.V.; Stevanović R.M. (Journal of the Serbian Chemical Society, 2007)
The electrochemical oxidation of methanol, 2-propanol, and their mixtures was investigated on a Pt/C thin film electrode in acid solution. It was confirmed that the oxidation of 2-propanol commences at less positive potentials than that of methanol and exhibits significantly higher oxidation current densities at low potentials. When both methanol and 2-propanol were present in the solution, the onset of the oxidation current was the same as for the oxidation of pure 2-propanol. Although both alcohols inhibit the oxidation reaction of each other to a certain extent, steady-state polarization measurements showed that their mixture provides higher current densities than single alcohols over the entire potential region from the hydrogen region to oxide formation on the Pt surface. This implies that the addition of 2-propanol into the fuel may extend the operational range of direct methanol fuel cells.